1999
DOI: 10.1210/mend.13.6.0297
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Models to Study Gonadotropin Function: The Role of Follicle-Stimulating Hormone in Gonadal Growth and Tumorigenesis

Abstract: The role of FSH in gonadal tumorigenesis and, in particular, in human ovarian cancer has been debated. It is also unclear what role the elevated FSH levels in the inhibin-deficient mouse play in the gonadal tumorigenesis. To directly assess the role of FSH in gonadal growth, differentiation, and gonadal tumorigenesis, we have generated both gain-of-function and loss-of-function transgenic mutant mice. In the gain-of-function model, we have generated transgenic mice that ectopically overexpress human FSH from m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
1
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(119 citation statements)
references
References 26 publications
5
112
1
1
Order By: Relevance
“…Testosterone ( (Kumar et al, 1999). In contrast to previous data (Risma et al, 1995) indicating that there is no difference in circulating LH levels between the TG and WT males, we show in the present report that LH levels are elevated in male bLHb-CTP mice, at least at the age of 9-12 weeks, but the elevation is less marked than in females and could be explained by the different age groups analysed.…”
Section: Discussioncontrasting
confidence: 99%
“…Testosterone ( (Kumar et al, 1999). In contrast to previous data (Risma et al, 1995) indicating that there is no difference in circulating LH levels between the TG and WT males, we show in the present report that LH levels are elevated in male bLHb-CTP mice, at least at the age of 9-12 weeks, but the elevation is less marked than in females and could be explained by the different age groups analysed.…”
Section: Discussioncontrasting
confidence: 99%
“…In comparison, ectopic FSH expression in the tg-hpg model independent of GnRH and LH (Allan et al 2004, Allan et al 2001, as well as preserved hormone responsiveness, allows further investigation of FSH in isolation or combined with other hormones. The confounding effects of supraphysiological FSH concentrations previously reported in tg-FSH mice (Kumar et al 1999) were not observed in this tg-FSH hpg model, since serum tg-FSH (4-5 IU/l) did not impede the fertility of young non-hpg females and was therefore within the limits compatible with physiological ovarian function (paper in preparation, Allan et al).…”
Section: Discussionmentioning
confidence: 61%
“…The influence of inhibin B on adult spermatogenesis is not apparent, as mice that cannot produce inhibin B due to deletion of the gene encoding the b B subunit are fertile (Vassalli et al 1994, Kumar et al 1999. However, the chronic absence of inhibin in the Inha K/K mouse (Matzuk et al 1992) leads to development Figure 1 Development of the mouse testis and realtime PCR analysis of inhibin/activin subunits and follistatin mRNA.…”
Section: Introductionmentioning
confidence: 99%